Innovative development of fire and rescue technical equipment in Republic of Belarus - Potekha, Валентин Леонидович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The present state in the field of the intellectual property in educational institutions of the Ministry for Emergency Situations, at the enterprises and the organizations of the Republic of Belarus is analyzed. It is shown, that for creation new, modem samples of fire and rescue technical equipment it is necessary to improve essentially a state of affairs in the field of the intellectual property by realization of the suggested organizational measures.